Facile one-step radio frequency magnetron sputtering of Ni/NiO on stainless steel for an efficient electrode for hydrogen evolution reaction - Ha Huu Do; Khac Binh Nguyen; Phuong N. Nguyen; Hoai Phuong Pham (Beilstein Journal of Nanotechnology)
The advancement of affordable, ultrastable, and efficient electrode materials for basic hydrogen evolution reaction (HER) plays a crucial role in industrial hydrogen manufacture, resolving problems caused by carbon dioxide emissions. Ni-based electrocatalysts have been well accepted as potential candidates to replace Pt-based electrocatalysts for HER because of their suitable Gibbs free hydrogen adsorption energy, good intrinsic catalytic properties, and high stability. However, solution-based synthetic approaches can be highly harmful to human beings. In this study, Ni/NiO nanolayers were prepared on stainless steel (SS) via a facile one-step radio frequency magnetron sputtering with various O2 flow rates. The O2 flow rate not only changed the crystal phase but also affected the morphology and atomic ratio of materials, leading to optimized HER efficiency. The evaluation of catalytic activities revealed that the optimal sample of Ni/NiO/SS-10 displayed a higher HER performance than bare SS. To produce H2 at a current density of 10 mA·cm−2, this electrode required a low overpotential of 184 mV and demonstrated remarkable durability over 12 h of operation. The high efficiency is attributed to the collaborative work of the NiO and Ni metal components and the good electrical conductivity of SS, which is advantageous for dissociative adsorption of water molecules, recombination of hydrogen atoms, and improvement of electronic/ionic motion. This work may introduce a facile and eco-friendly strategy for fabricating noble metal-free, efficient nanomaterials for electrocatalytic HER.